The Impact of Parasocial Interaction and Local Presence on Impulsive Buying Behavior on TikTok - Laurencia Feby; Fahrul Riza; Dwi Anna Kristanti (Jurnal Ilmiah Manajemen Kesatuan, 2024)
TikTok, as a social media platform, has significant potential to influence consumer purchasing decisions through content creators and live streaming features. Live streaming facilitates parasocial interactions with hosts and co-viewers, as well as local presence, which can impact consumers' perceived product values and impulsive buying behavior. This study examines the effects of parasocial interactions, both with hosts and co-viewers, and local presence on utilitarian and hedonic values, ultimately leading to impulsive buying behavior. Using a quantitative approach, data were collected through questionnaires distributed to respondents selected through purposive sampling. Analysis was conducted using Structural Equation Modeling (SEM) with the assistance of SmartPLS. The results revealed that parasocial interactions and local presence significantly influence consumers’ perceived values, which in turn affect their impulsive behavior. These findings contribute to the literature by highlighting the mediating role of these values in the relationship between social elements and impulsive behavior. Further research is encouraged to explore these dynamics in greater depth, as well as to examine differences across various platforms and cultural contexts.